ATIVIDADE MICROBIANA E ESTABILIDADE DE AGREGADOS EM SISTEMAS INTEGRADOS DE PRODUÇÃO AGROPECUÁRIA - BARBOSA, Ygor Iahnn,; COÊLHO, Roseline da Silva,; DUARTE, Isis Caroline da Silva1 (isis.carolini@hotmail.com,; OLIVEIRA, Naelmo de Souza,; SCHIAVO, Jolimar Antonio, (ANAIS DO ENIC, 2023)
-